Natural fiber and aluminum sheet hybrid composites for high electromagnetic interference shielding performance. (1st April 2017) - Xia, Changlei; Yu, Jason; Shi, Sheldon Q.; Qiu, Ying; Cai, Liping; Wu, H. Felix; Ren, Han; Nie, Xu; Zhang, Hualiang
Abstract: Using natural fiber mats, aluminum sheets and epoxy resin, hybrid composites were fabricated through vacuum assisted resin transfer molding (VARTM) process. With novel sandwich structures, these hybrid composites contain natural fiber-based shells and ultra-thin aluminum sheet core. The hybrid composites offered excellent electromagnetic interference (EMI) shielding performance with good mechanical properties inherited from aluminum sheets and natural fiber-based composites, respectively. Furthermore, the shell material (natural fiber-based composites) provides protection of the aluminum sheets from exposing to atmosphere directly to prevent being corroded. In this study, the EMI shielding effectiveness, microstructure, flexure property, tensile property, and internal bonding strength of the hybrid composites were examined. The excellent EMI shielding performance and good mechanical properties enable the new hybrid composites to be used as engineering materials in the EMI protection fields. Highlights: A novel multifunctional composite with hybrid sandwich-structure was developed. One-step vacuum assisted resin transfer molding for the composites fabrication. Al sheets as cores endow excellent electromagnetic interfacial (EMI) shielding. Hemp/epoxy as shells provide great mechanical properties and corrosion protection. This EMI shielding composite owns sustainable, effective, and economical properties.